2006
DOI: 10.1161/01.str.0000195046.89926.98
|View full text |Cite
|
Sign up to set email alerts
|

Novel Representation of Astasia Associated With Posterior Cingulate Infarction

Abstract: Background and Purpose-The representation elicited in the cingulate motor area has been demonstrated in animals, but remains unclear in humans. In particular, the representation and pathogenic mechanisms of the posterior cingulate cortex are poorly understood, especially in humans. We describe a case of posterior cingulate infarction associated with contralateral astasia. Case Description-A 67-year-old right-handed man with a 10-year history of hypertension suddenly presented with right-sided pulsion on attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 12 publications
2
22
0
Order By: Relevance
“…Contralateral astasia associated with medial frontal lesions has rarely been described, and recently, only one case has been reported 4. Kataoka et al 4 described a patient with posterior cingulate infarction who showed contralateral pulsion similar to that of our patient.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Contralateral astasia associated with medial frontal lesions has rarely been described, and recently, only one case has been reported 4. Kataoka et al 4 described a patient with posterior cingulate infarction who showed contralateral pulsion similar to that of our patient.…”
Section: Discussionsupporting
confidence: 58%
“…They also described that thalamic astasia may mimic cerebellar disease. In other reports of astasia associated with other lesions, the direction of astasia was also contralateral to the site of lesions, such as the midbrain or posterior cingulate region 4 6…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Specifically, O-W women showed significantly weaker activation than leaner women did within the posterior ventral cingulate cortex (left BA 23) in the exerciselandscape contrast and marginally stronger middle frontal gyrus (BA 6) activation in the sedentary-landscape contrast, both of which are areas implicated in motor learning and movement. [51][52][53][54] Activation of the posterior ventral cingulate cortex is also related to autobiographical memory, kinesthetic memory of body movements, storage of motion velocity, visuospatial orientation and navigation of the body in environmental space. [55][56][57][58] Vann et al 59 reported areas 23 and 31 are more active during retrieval of real than imagined events, contending that re-experiencing real events modulates activity in this area.…”
Section: Discussionmentioning
confidence: 99%
“…It resembles the marked balance impairment of patients with vestibulocerebellar disease [4] . The responsible anatomical region for astasia or astasia-abasia has been known to be related to the thalamic lesion affecting mainly the medial ventrolateral nucleus of the thalamus because the fastigial fibers of the vestibulocerebellar pathway project to the medial ventrolateral nucleus, and disruption of this pathway may cause thalamic astasia [6] . Inability to walk despite good motor strength was also reported in a patient with a red nucleus infarction involving the ascending fibers of the crossed dentatorubrothalamic tract, in a patient with a small medial capsular hemorrhage extending to the lateral portion of the ventrolateral nucleus of the thalamus and in a patient with a hemorrhage at the pontomesencephalic junction (midbrain tegmental lesion) involving the pedunculopontine area [7][8][9] .…”
Section: Discussionmentioning
confidence: 99%